Integrated and concurrent detailed design of a mechatronic quadrotor system using a fuzzy-based particle swarm optimization. (June 2019) - Mohebbi, Abolfazl; Achiche, Sofiane; Baron, Luc
Abstract: Mechatronics design is complex by nature as it involves a large number of couplings and interdependencies between subsystems and components alongside a variety of sometimes contradicting objectives and design constraints. Mechatronics design activity requires cross-disciplinary and multi-objective thinking. In this paper, a fuzzy-based approach for the modeling of a unified performance evaluation index in the detailed design phase is presented. This index acts as a multidisciplinary objective function aggregating all the design criteria and requirements from various disciplines and subsystems while taking into account the interactions and correlations among the objectives. Then this function is optimized using a particle swarm optimization algorithm alongside all the constraints facing each subsystem. As an application, the mechatronics design of a vision-guided quadrotor unmanned aerial vehicle is carried out to demonstrate the effectiveness of the proposed method. Thus, a thorough modeling of system dynamics, structure, aerodynamics, flight control and visual servoing system is carried out to provide the designer with all necessary design variables and requirements. The final results and related computer simulations show the effectiveness of the proposed method in finding solutions for an optimal mechatronic design.